Sociodemographic correlates of physical activity and screen time among adolescents in Canada and Guatemala: Results from the COMPASS system. (June 2019) - Lee, Eun-Young; Hunter, Stephen; Leatherdale, Scott T.; Carson, Valerie
This study was to compare the levels of physical activity (PA) and sedentary behavior (SB) between Canadian and Guatemalan adolescents, and to examine associations of sociodemographic variables with PA and screen time among adolescents in Canada and Guatemala. Self-reported, cross-sectional data from students in grades 9–12 who participated in the 2015 COMPASS study (Canada; n = 39, 817; mean age = 15.6 years) and COMPASS-Guatemala ( n = 1, 221; mean age = 15.1 years) were used. Sociodemographic variables included age, gender, ethnicity (exclusively among Canadians), and weekly money allowance. Outcome variables included meeting the PA guidelines (⩾60 minutes/day) and the screen time recommendations within the SB guidelines (<2 hours/day), and participation in organized sports in and out of school. Chi-squared tests and linear and logistic regressions were used to test the study objectives. The proportions of participants meeting the PA guidelines were 48.7% and 41.3% for Canadians and Guatemalans, respectively. More Guatemalan adolescents than Canadians met the screen time recommendations (24.9% vs. 16.5%). Older age, being male, being non-White, and $0–$5/unknown of allowance were associated with meeting the PA guidelines among Canadians. Gender (being male) was the only variable associated with meeting the PA guidelines among Guatemalan adolescents. Older age, being male, being non-White, and $0–$5/unknown of allowance were associated with organized sport participation among Canadians. Among Guatemalans, being aged 15–16 years and having 0–35 quetzals/unknown of allowance were associated with participating in competitive school sports. Being male was associated with participating in recreational school sports or league/team sports outside of school. Older age, being female, being non-White, and ⩾$6 of allowance were associated with meeting the screen time recommendations among Canadians. Older age and having ⩾150 quetzals of allowance were associated with meeting the screen time recommendations among Guatemalan adolescents. These findings can inform researchers and policy makers when developing country-specific targeted interventions and programs that promote physically active lifestyles.